2016
DOI: 10.1038/srep28781
|View full text |Cite
|
Sign up to set email alerts
|

Common molecular mechanism of amyloid pore formation by Alzheimer’s β-amyloid peptide and α-synuclein

Abstract: Calcium-permeable pores formed by small oligomers of amyloid proteins are the primary pathologic species in Alzheimer’s and Parkinson’s diseases. However, the molecular mechanisms underlying the assembly of these toxic oligomers in the plasma membrane of brain cells remain unclear. Here we have analyzed and compared the pore-forming capability of a large panel of amyloid proteins including wild-type, variant and truncated forms, as well as synthetic peptides derived from specific domains of Aβ1-42 and α-synucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
160
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 64 publications
6
160
0
Order By: Relevance
“…This view agrees with our recent data showing a reduced mobility of GM1 molecules in GM1-enriched neuronal cells by Single Molecule Tracking (SMT) experiments [8]. Our data also agree with several reports indicating that the cholesterol content affects membrane physical features such as fluidity and GM1 clustering, hindering both aggregate recruitment at the cell membrane and membrane permeabilization [63,65]. Overall, our results indicate that age-dependent clustering of membrane GM1 in neurons, a well-known alteration in the AD brain [3], can represent a risk for neurodegeneration in elderly people as a consequence of an increased ability of the lipid components of the bilayers to recruit membranepermeabilizing oligomers without any involvement of specific receptors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This view agrees with our recent data showing a reduced mobility of GM1 molecules in GM1-enriched neuronal cells by Single Molecule Tracking (SMT) experiments [8]. Our data also agree with several reports indicating that the cholesterol content affects membrane physical features such as fluidity and GM1 clustering, hindering both aggregate recruitment at the cell membrane and membrane permeabilization [63,65]. Overall, our results indicate that age-dependent clustering of membrane GM1 in neurons, a well-known alteration in the AD brain [3], can represent a risk for neurodegeneration in elderly people as a consequence of an increased ability of the lipid components of the bilayers to recruit membranepermeabilizing oligomers without any involvement of specific receptors.…”
Section: Discussionsupporting
confidence: 83%
“…The affinity of protein aggregates for membrane GM1 was suggested to involve the negative charge of the sialic acid [63,64]. Our results agree with these considerations; in fact, we showed that A␤ 42 oligomers display an increased tendency to interact with SUVs as far as GM1 abundance is raised, supporting the idea that aggregate binding is not only driven by the presence of membrane protein targets [64].…”
Section: Discussionsupporting
confidence: 82%
“…Knowledge of this structural ensemble is interesting not only to design inhibitors, 72,73 but also to understand the interactions with many cellular partners in early stage Alzheimer’s disease. 4,7477 …”
Section: Discussionmentioning
confidence: 99%
“…The topic of amyloidogenesis has been the subject of many scientific endeavors and a great variety of papers have been published, approaching the problem from all possible angles: diagnostics [63][64][65][66], therapeutic [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] and structural/molecular [82][83][84][85]. Our publication does not, however, discuss amyloidogenesis as such, but rather the molecular processes which lead to the formation of fibrillary aggregates commonly referred to as amyloids.…”
Section: Discussionmentioning
confidence: 99%